Utilization Of Butterfly Pea Flowers (Clioria ternate L.) In Gram Staining Of Staphylococcus aureus and Escherichia coli Bacteria - DIAN HASTARI NINGRUM; Herlina Herlina; Visensius Krisdianilo; Andy Febriady (Institut Kesehatan Medistra Lubuk Pakam, 2024)
Introduction : Butterfly pea flower (Clitoria ternatea L.) is one of the most commonly found plants. Butterfly pea flowers contain anthocyanins which are abundant in the flowers and play a role in giving red, violet-blue color to the flowers. Anthocyanins are the main molecules of plant colorants. The potential of anthocyanins in butterfly pea flowers can be used as a natural coloring reagent. Objective : The purpose of this study was to determine whether telang flower extract can be used as a substitute for gentian violet in Gram staining. Method : The research method used is experimental. Result : The results of Gram staining research using original pH butterfly pea flower extract at concentrations of 1:10, 2:10, 3:10, 4:10, and pH 5 butterfly pea flower extract at concentrations of 1:10, 2:10, 3:10, 4:10, 5:10 on Staphylococcus aureus bacteria showed poor bacterial staining results because the bacteria were not purple while the original pH butterfly pea flower extract at a concentration of 5:10 showed good staining results because the bacteria were purple. While in Escherichia coli bacteria, butterfly pea flower extract shows good staining results because the bacteria are red. Conclusion : Data analysis using the Kruskal Wallis test obtained Asymp. Sig (0.000) <0.05, it can be concluded that there is a significant difference in Gram staining using gentian violet and telang flower extract with variations in pH and composition as a substitute for gentian violet.